INTERDISCIPLINARY APPROACH OF ISLAMIC PSYCHOLOGY LITERACY IN INDONESIA - Dede Rosyada; Abdul Mujib; Syahidah Rena (Psikis : Jurnal Psikologi Islami, 2020)
The development of journal literacy with the theme of Islamic Psychology used a lot of typologies in the madhab of psychology, including Islamic Psychoanalysis, Islamic Psycho-behavioristic, Islamic Psychohumanistic, Islamic Psychocognitive, and Islamic Psychotranspersonal. This study aims to analyze the types of madhab integration in constructing journal literacy in the areas of Islamic psychology in Indonesia. Thus, the tendency could be known and be a guideline in the development of Islamic psychology later on. As library research that used content analysis techniques, this study found that although the journal writers had diverse typologies in the development of the Islamic Psychology madhab, the study showed that the Transpersonal madhab dominated the pattern of developing Islamic psychology in the journaling system in Indonesia.This tendency is due to the process of Islamic integration, the easiest psychology, and the lowest resistance level is integrating Psychotranspersonal with Islamic sciences. Psychotranspersonal themes are more easily developed through literary research and/or qualitative research, while other madhabs claim more to quantitative research.